Determinan Earnings Response Coefficient (ERC) - Ramadhanti, Ella; Mutiara, Intan; Syafadan, Ayu (Systematic Literature Review Journal, 2025)
This study examines the Earnings Response Coefficient (ERC) as an indicator of market reaction to earnings announcements, focusing on several determining factors: Corporate Social Responsibility (CSR), financial distress, corporate growth, firm size, and earnings persistence. The primary issue addressed is the inconsistency of previous empirical findings regarding the influence of these factors on ERC, which motivates this study to reassess these relationships through a Systematic Literature Review (SLR) approach. The SLR method was employed to systematically collect, analyze, and synthesize evidence from prior studies to obtain a more comprehensive understanding. The findings reveal that CSR and earnings persistence produce mixed results—some studies show positive, negative, or insignificant effects on ERC—reflecting contextual differences and variations in investor perceptions. Meanwhile, financial distress and firm size generally have a significant positive impact on ERC, suggesting that larger firms and those perceived as financially stable are more likely to receive stronger market reactions. Corporate growth, on the other hand, mostly shows no significant effect. The synthesis highlights that the relationship between these factors and ERC is context-dependent, influenced by company characteristics and the level of information transparency provided to investors. This study concludes by emphasizing the need for a more integrative and contextual approach in analyzing the determinants of ERC and recommends further research to deepen understanding of how market responses to earnings information are shaped by these factors.